Conjugated Porous Polymers: Ground‐Breaking Materials for Solar Energy Conversion. Issue 43 (1st August 2021) - Barawi, Mariam; Collado, Laura; Gomez‐Mendoza, Miguel; Oropeza, Freddy E.; Liras, Marta; de la Peña O'Shea, Victor A.
Abstract: Solar energy conversion plays a very important role in the transition to a more sustainable energy system. In this sense, so many systems have been proposed to drive artificial photosynthesis, most of them based on inorganic semiconductors, and the achievements performed continue every day. However, most of these systems present well‐known shortcomings as low light absorption, fast charge recombination, and lack of tunability, thus limiting their efficiency. The use of organic polymers in general and conjugated porous polymers (CPPs) in particular, opens the door to a multitude of new possibilities when it comes to design and selection of a suitable photocatalyst. CPPs exhibit improved light harvesting, charge conduction properties, high photochemical stability, and high surface area that make them ideal for photocatalytic applications. Here, the use of CPPs and hybrids as photocatalysts for solar energy conversion in the hydrogen evolution reaction and the CO2 reduction reaction and its use as a photoelectrode are reviewed. The photocatalytic properties are focused upon here. The photophysics related to these applications is also discussed. Finally, a perspective is provided, proposing an in situ and operando characterization methodology that is expected to allow improvements to their optoelectronic properties and thereby their future design and applicability. Abstract : Conjugated porous polymers are one of the most interesting alternatives to convert solar energy into fuels due to their interesting optoelectronic properties. The state of the art of conjugated porous polymers is reviewed, and a methodology for their advanced characterization and an in situ and operando mechanistic investigation is proposed, allowing advancement in the understanding of their use as photocatalysts and consequently an improvement in their conversion efficiencies.